THE EFFECTIVENESS OF TALKING CHIPS TO TEACH SPEAKING VIEWED FROM STUDENTS’ INTELLIGENCE - Muhammad Iqbal Ripo Putra (IKIP PGRI Pontianak, 2015)
AbstractThis article refers to an experimental study about the effectiveness of talking chips to teach speaking at an English Education Department of a University in Pontianak, West Kalimantan. The sample of this research consists of two classes; class A was used as the experimental group treated by using Talking Chips method and class B as the control group treated by using peer tutoring method. The sampling technique used is cluster random sampling. The instruments used to collect the data are students’ documents of intelligence test and speaking test. The data were analyzed by using multifactor analysis of variance (ANOVA 2X2) and Tukey test. Based on the above findings, it can be concluded that talking chips method is an effective method to teach speaking for the first semester students of the English Education Department of a University in Pontianak. The effectiveness of the method is influenced by the students’ level of intelligence. Based on the research findings, in general it can be concluded that Talking Chips is an effective method to teach speaking. Keyword: Speaking Skill, Talking Chips Method, Peer Tutoring Method, Intelligence Quotient, Experimental Study.